Деякі методичні питання навчання граматики української мови на початковому етапі - Ліпатова, М. В.; Бабич, Т. В.; Lipatova, M.; Babich, T. (ЦДПУ ім. В. Винниченка, 2020)
Стаття присвячена питанням навчання граматики української мови як іноземної і формування граматичної компетенції студентів - іноземців. Під час вивчення граматики студенти опановують граматичним матеріалом, необхідним для вираження думок в усній та письмовій формі і розуміння їх при читанні і на слух. У статті визначено основні етапи введення граматичного матеріалу на заняттях з української мови як іноземної. The article deals with problems of the formation of grammatical competence as an important component of foreign language communicative competence, the theoretical principles and foundations that are relevant for the Ukrainian as a foreign language teaching methods at the advanced stage of training have been analyzed. The article concerns the aspect of Grammar as an important part of any language which ensures the formation of oral and written communication skills. The study of the issue which is discussed in the article is relevant, since the formation of grammatical skills is one of the prerequisites for developing the ability to express their thoughts in oral and written forms, as well as the ability to understand the views expressed by other people, which is important for the communication process. Grammar is the part of the content of Ukrainian as a foreign language teaching program, therefore its role is seen in the aspect of learning activities, since grammar should contribute to the formation and development of speech skills, to play a supporting role for grammar rules and structures to serve communicative learning purposes. The grammar skills formation in foreign language learners is one of the most important components of speaking, listening, reading and writing teaching process. Studying grammar material it is necessary to form grammar skills for oral speech, which provide grammatically correct structure of dialogue and monologue speech. The need to study grammar in practical use is emphasized. The main purpose of teaching grammar as seen by the communicative method is the formation of communicative competence meaning student’s ability to act in accordance with a variety of life situations. It is a sine qua non condition that the exercises should be of interest and lead to the formation of free speech. That can promote successful communication.
Some Methodological Problems of Teaching the Grammar of the Ukrainian Language at the Initial Stage
Keywords: граматична компетенція; активна і пасивна граматика; граматичні навички; мовні вправи; мовленнєві вправи; комунікативні цілі навчання; teaching of grammar; grammatical competence; grammar skills formation; oral and written communication; communication goals of teaching; passive and active grammar minimum; stages of forming skills